DETEKSI WARNA KULIT DAN REKOMENDASI PALET WARNA BERDASARKAN SEASONAL COLOR MENGGUNAKAN CNN - Adzkia, Hawarizmi Ummul; Asriyanik, Asriyanik (Universitas Palangka Raya, 2025)
The Personal Color trend has grown significantly, assisting individuals in selecting clothing colors that complement their skin tone. This research aims to develop a system using Convolutional Neural Networks (CNN) to detect skin tones from photos and recommend color palettes based on Seasonal Color Theory. The system categorizes skin tones into the four seasonal types: Winter, Summer, Autumn, and Spring, and provides tailored clothing color suggestions. By applying machine learning, this system offers a personalized solution for clothing selection, enhancing the shopping experience. It aligns with the growing popularity of Personal Color trends, helping users make more confident and informed color choices that suit their individual characteristics.